2022
DOI: 10.37689/acta-ape/2022ao01902
|View full text |Cite
|
Sign up to set email alerts
|

Associação entre a síndrome de burnout e a violência ocupacional em professores

Abstract: Conflitos de interesse: nada a declarar. ResumoObjetivo: Verificar a associação entre a violência laboral e a síndrome de burnout em professores.Métodos: Estudo transversal realizado com 200 professores do Ensino Fundamental e Médio de um município paranaense. Os dados foram coletados por meio de um instrumento contendo um questionário com dados sociodemográficos, ocupacionais e de caracterização da violência laboral sofrida ou testemunhada nos últimos 12 meses e o Maslach Burnout Inventory para avaliar a sínd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 22 publications
0
3
0
2
Order By: Relevance
“…However, it was worth noting that the experience of witnessing workplace violence negatively correlated with DPA in all three samples. While several studies conducted among teachers have suggested that witnessing workplace violence is associated with both EE and DPA positively ( 47 49 ), differences between teachers and healthcare workers have emerged. Even though experiencing or witnessing workplace violence was prevalent among teachers and healthcare workers ( 47 , 50 ), workplace violence was mostly perpetrated by students and their parents in the former group ( 48 ), whereas in the latter group, most violence was perpetrated by patients or patients' families ( 50 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it was worth noting that the experience of witnessing workplace violence negatively correlated with DPA in all three samples. While several studies conducted among teachers have suggested that witnessing workplace violence is associated with both EE and DPA positively ( 47 49 ), differences between teachers and healthcare workers have emerged. Even though experiencing or witnessing workplace violence was prevalent among teachers and healthcare workers ( 47 , 50 ), workplace violence was mostly perpetrated by students and their parents in the former group ( 48 ), whereas in the latter group, most violence was perpetrated by patients or patients' families ( 50 ).…”
Section: Discussionmentioning
confidence: 99%
“…While several studies conducted among teachers have suggested that witnessing workplace violence is associated with both EE and DPA positively ( 47 49 ), differences between teachers and healthcare workers have emerged. Even though experiencing or witnessing workplace violence was prevalent among teachers and healthcare workers ( 47 , 50 ), workplace violence was mostly perpetrated by students and their parents in the former group ( 48 ), whereas in the latter group, most violence was perpetrated by patients or patients' families ( 50 ). Furthermore, it should be noted that witnessing workplace violence physically or emotionally, which has not been distinguished in our study, could have a different psychological impact on healthcare workers which indicates that emotional workplace violence could be accepted or normalized by nurses ( 51 ).…”
Section: Discussionmentioning
confidence: 99%
“…Outro estudo transversal realizado com 200 professores do ensino fundamental e médio de um município no Pará mostrou que 57,5% dos professores apresentaram alta exaustão emocional, 49% alta despersonalização e 36% baixa realização profissional e 21% possuíam indicativo para síndrome de Burnout 18 .…”
Section: Discussionunclassified
“…The systematic literature review carried out by Silva and Negreiros (2020) evidences that violence in Brazilian public schools is a serious problem that needs to be addressed. Ribeiro et al (2022) observed an association between burnout syndrome in teachers and occupational violence, indicating the importance of working with prevention and intervention strategies.…”
Section: Teacher Illnessmentioning
confidence: 98%